The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1742-6596/1299/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Green Economy: The Role of Estate Surveyors and Valuer

Abstract: The continuous existence of man is dependent on the free goods and services (e.g. water, air purification, fisheries, timber production and nutrient cycling) provided by his natural environment. Due to the public nature of these goods and services, they are not traded in the open markets hence, they are regarded as not having market prices. As a result, the current economic system fails to capture their losses and this may continue for long if care is not taken. Unless economic decisions (and the associated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Correspondingly, the United Nations Environment Program (UNEP) clarifies the idea of green in real estate as the total commitment to both the social and environmental aspects that will result in low carbon development or sustainable development (UNEP, 2011). Furthermore, the literature has documented that green real estate investment is poised for constant growth in the coming years, supported by the increase in green real estate development projects since 2009 based on the increasing trend of the certified number of green building projects (Ajibola, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, the United Nations Environment Program (UNEP) clarifies the idea of green in real estate as the total commitment to both the social and environmental aspects that will result in low carbon development or sustainable development (UNEP, 2011). Furthermore, the literature has documented that green real estate investment is poised for constant growth in the coming years, supported by the increase in green real estate development projects since 2009 based on the increasing trend of the certified number of green building projects (Ajibola, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental Concern. The first motivation bonds to the rising concern of climate change, particularly for environmental degradation (Ajibola et al, 2019;Fan & Zhou, 2019;Xiao et 2017). Recent research by Kim et al (2020) has revealed that investors-owned have tendencies to own certified green buildings, which benefits the environment.…”
Section: The Conceptual Framework Of Motivations Of Green Real Estate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have therefore been made to use some of the contemporary valuation techniques such as the hedonic, contingent, conjoint, multiple regression, and PROBIT to assess the contamination and stigma effects of oil spillage, landfills, nuclear power plants, and hazardous waste sites, among others, on property values, but regrettably with conflicting results (Mundy, 1992;Otegbulu, 2011). Ajibola et al (2019) assert that, even though such are not traded in the open markets and therefore are regarded as having no marketplace prices, the values of natural goods and services still need to be assessed, especially when there is need to compensate affected persons, because man's continuous survival is dependent on the goods and services provided by the natural environment. They further state that future economic growth and development itself is endangered by environmental degradation, especially land contamination by oil spills as is common in the study area.…”
Section: Approaches To Valuing Oil Spill Contaminated Landmentioning
confidence: 99%
“…Ajibola, Oluwunmi, Kabiamaowei, Owolabi and Akinwale (2019) were of the view that man's continuous existence is hinged on the goods and services provided by the natural environment. Since these natural goods and services are not traded in the open markets they are therefore regarded as having no marketplace prices.…”
Section: Literature Reviewmentioning
confidence: 99%